Using Russian Ruble in International Transactions - I. Z. Yarygina (Vestnik MGIMO-Universiteta)
The article deals with topical issues in international relations of the Russian Federation on the basis of the increased use of the ruble as the currency contracts and payments. The work shows the coordinated support of economic actors, public institutions of countries-partners. Collaborate with international teams, according to the author of the article, the implementation of economic programs of mutual interest and reinforces the trend of creating a multipolar world. The analysis of problems of development cooperation partners countries in the monetary sphere and shows that the main causes hindering greater use of domestic currencies are: hard currency regulation; a rare use of letters of credit and guarantees, which increases the financial risk operations; significant transaction costs; asymmetrical measures, currency regulation, burdening the mutual interests of the parties. To expand the use of the ruble in international relations author offers take into account a number of factors, including the need for a priority international currency contracts to perform the basic functions of money abroad is a measure of the value, means of payment and means of hoarding. The author's position is presented about the prospects of State institutional policy. In particular, the conclusion: the experience of Bulgaria, Romania, Albania has shown that the main task of the departments responsible for implementing the monetary policy should be the containment of inflationary pressures associated, including overdue contributions to the budget. A key priority in such circumstances is to support solvent and transparent banking systems, which are the basis for international cooperation.